The Study of Pedestrian’s Convenience and Privacy Towards Pandanaran Crossing Bridge Condition - Djoko Indrosaptono; Alfanadi Agung Setiyawan (Journal of Architecture & Environment, 2021)
One of the urban infrastructures that reflect the development of a city is a Crossing Bridge. If a city is more developed, the activity of human movement between regions will increase. Crossing Bridge, which is one of the Street Furnitures, functions to ease the people's mobility safely without distracting the flow of existing vehicles. In fact, Crossing Bridge have not been optimally utilized by pedestrians, it can be seen by pedestrian behavior that is applied when passing through the highway by jumping over the barrier. As happened on the Pandanaran road section in the city of Semarang, this behavior causes the bridge to malfunction and brings up further phenomena such as stairs changing into seats and circulating bridges being occupied by homeless people. The purpose of this research is to uncover the connection between the privacy attributes and pedestrian convenience, with the setting conditions of the Pandanaran Crossing Bridge in Semarang, by using a quantitative paradigm approach. The results of the questionnaire in closed form and the Behavioral Mapping method will then be analyzed using descriptive statistical analysis techniques, until it will finally be revealed that the lack of property strength on the Crossing Bridges, which is not able to meet the pedestrians' attribute needs, causes some people choose to cross directly.